Synthesis,magnetic properties, and catalytic properties of a nickel(II)-dependent biomimetic of metallohydrolases - Horn, Adolfo, Jr.; Englert, Daniel; Roberts, Asha E.; Comba, Peter (Frontiers in Chemistry, 2018)
A dinickel(II) complex of the ligand 1,3-bis(bis(pyridin-2-ylmethyl)amino)propan-2-ol (HL1) has been prepared and characterized to generate a functional model for nickel(II) phosphoesterase enzymes. The complex, [Ni2(L1)(OAc)(H2O)2](ClO4)2·H2O, was characterized by microanalysis, X-ray crystallography, UV-visible and IR absorption spectroscopy and solid state magnetic susceptibility measurements. Susceptibility studies show that the complex is antiferromagnetically coupled with the best fit parameters J = -27.4 cm-1, g = 2.29, D = 28.4 cm-1, comparable to corresponding values measured for the analogous dicobalt(II) complex [Co2(L1)(OAc)](ClO4)2·0.5 H2O ( J = -14.9 cm-1 and g = 2.16). Catalytic measurements with the diNi(II) complex using the substrate bis(2,4-dinitrophenyl)phosphate (BDNPP) demonstrated activity toward hydrolysis of the phosphoester substrate with Km =11 ± 2 mM, and kcat = 2.5 ± 0.05 x 10-5 s-1. The combination of structural and catalytic studies suggests that the likely mechanism involves a nucleophilic attack on the substrate by a terminal nucleophilic hydroxido moiety.
Gesehen am 13.06.2019